2019
DOI: 10.11114/jets.v7i2.3840
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Hyperactivity and Attention Deficit of University Students Who Do Sport Regularly and Do Not Do Sport in Terms Of Some Variances

Abstract: Introduction: Hyperactivity and attention deficit are situations which have been seen in individuals recently and affect both academic and life quality of individual negatively. The aim of this study is to determine hyperactivity and attention deficit level of university student who sport regularly and do not sport.Method: Carried out with scanning model, this study was applied to 353 students, who continue their education at Yuzuncu Yil University during 2017/2018 academic year, including 208 students who spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…The students who graduated from a sports high school reported higher levels of ADHD symptoms. In contrast, the study conducted by Özkan & Arslan (2019) did not show a significant difference for "high school graduated" variable.…”
Section: Conclusion and Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The students who graduated from a sports high school reported higher levels of ADHD symptoms. In contrast, the study conducted by Özkan & Arslan (2019) did not show a significant difference for "high school graduated" variable.…”
Section: Conclusion and Discussionmentioning
confidence: 56%
“…The study conducted by Doğan et al (2008) with university students found that ADHD symptoms negatively affected academic and psychological functionality. Also, Özkan & Arslan (2019), in their study, examined academic performance in terms of hyperactivity symptom levels and found a significant difference in favor of the participants reporting a "very good" academic performance.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
See 1 more Smart Citation